2017
DOI: 10.18632/oncotarget.18100
|View full text |Cite
|
Sign up to set email alerts
|

Total fluid consumption and risk of bladder cancer: a meta-analysis with updated data

Abstract: With meta-analysis we tented to reveal the potential relationship between daily fluid consumption and bladder cancer risk, and to find out a recommendation on daily fluid intake. Databases of the Web of Science, PubMed and EMBASE were searched then 21 case-control and 5 cohort studies were included. Stratified analyses on gender, region, time of subjects recruiting and fluid quantity were performed as well as dose-response meta-analysis. Comparing the highest exposure category with the lowest in each study, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
(54 reference statements)
0
10
0
1
Order By: Relevance
“…People who drink a lot of fluids each day, especially water, tend to have lower rates of bladder cancer (1.4 L/day compared with 0.4 L/day) [ 16 , 17 , 18 ]. On the other hand, a meta-analysis confirmed that the high daily fluid intake might be associated with high BC risk in European and American males, and a limitation of fluid consumption to <2000 mL and <3000 mL per day is recommended, respectively [ 19 ]. Bladder cancer occurrence is also associated with age—the median age at diagnosis is 69 years for men and 71 years for women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…People who drink a lot of fluids each day, especially water, tend to have lower rates of bladder cancer (1.4 L/day compared with 0.4 L/day) [ 16 , 17 , 18 ]. On the other hand, a meta-analysis confirmed that the high daily fluid intake might be associated with high BC risk in European and American males, and a limitation of fluid consumption to <2000 mL and <3000 mL per day is recommended, respectively [ 19 ]. Bladder cancer occurrence is also associated with age—the median age at diagnosis is 69 years for men and 71 years for women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to fluid intake and the risk of developing bladder cancer for the first time, the results of a recent case-control study have shown that there was no association with total water intake from both beverages and foods [ 20 ]. Also the results of a meta-analysis demonstrated no association between total fluid intake and the risk of developing primary bladder cancer [ 21 ]. However, subgroup analyses indicated that high fluid intake could increase the risk of bladder cancer in European men (and possibly American men) and decrease the risk of bladder cancer in Asian men [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also the results of a meta-analysis demonstrated no association between total fluid intake and the risk of developing primary bladder cancer [ 21 ]. However, subgroup analyses indicated that high fluid intake could increase the risk of bladder cancer in European men (and possibly American men) and decrease the risk of bladder cancer in Asian men [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Casi la tercera parte señaló tomar 4 vasos de agua natural al día. Al respecto se ha reportado una mínima reducción de enfermedad cardiovascular en los que toman cinco o más vasos de agua diarios (21) y se ha encontrado asociación entre la ingesta total de líquidos y el riesgo de cáncer (22) . También se señala que las recomendaciones del consumo de agua diferente a otros líquidos, no son concluyentes y es diferente en cada persona (23) .…”
Section: Años Con Enfermedadunclassified